Inklusi Keuangan dan Kondisi Keuangan Negara Berkembang Sebagai Penentu Stabilitas Sektor Finansial - Pertiwi, Anisa; Satria, Doni (Universitas Negeri Padang, 2025)
Financial inclusion has an important role in encouraging banking competition which illustrates the potential for economics benefits both micro and macro levels. Each country has structural characteristics that can be boosters or obstacles to the acceleration of financial inclusion. It is difficult to say that a country has a stable financial condition, because the huge financial system tends to be more vulnerable to crises and instability. This study aims to analyze the impact of financial inclusion on financial system stability in 40 developing countries from 2005-2021. Based on the type of data and the form of the equation, this study uses the Dynamic Panel Data analysis method with the Generalized Method of Moment approach. This study uses the System General Method of Moment (SYS GMM) two-step estimator. The results show financial system stability of developing countries is influenced by the global economics policy uncertainty, so that the shock at the global level will have an impact on domestic economic instability. Financial inclusion through the use of financial services can encourage financial system stability because it shows the financial depth and resilience of the central bank in the face of shocks. However, financial inclusion through the availability of access to financial institutions can cause instability in the financial system because ease of access tends to encourage people in developing countries to borrow excessively and have an impact on the instability of the financial system.